PEMANFAATAN MEDIA KOMUNIKASI WHATSAPP UNTUK PENINGKATAN GOTONG ROYONG LK 4 BANGUN REJO KELURAHAN SINDANG SARI LAMPUNG - Lovia Evanne; Yulina Yulina (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The essence of communication is a process of sharing information, thoughts, and feelings between people through conversation, writing, or body language. Interpersonal communication aims to create a common perception, change behavior and obtain information. It is essential to study communication media to deal with conflict. Humans, as social beings, cannot be separated from their social function. This is in line with Maslow's third-order theory, namely the social need to be loved and cared for. It is impossible if socialization is done without communication. Along with the sophistication of technology, to be able to change face-to-face communication into mediated communication. Whatsapp is one of the virtual communication media. The WhatsApp communication media utilization program is a communication medium that has been massively used but has yet to be optimally used for the benefit of LK 4 Bangun Rejo, Sindang Sari Village, Lampung. The purpose of the WhatsApp communication media utilization program is for participants to use WhatsApp communication media and to increase cooperation in LK 4 Bangun Rejo, Sindang Sari Village, Lampung. In the end, this activity is expected to make the team dedicated to the community's needs and have a social-human spirit according to information and communication technology development.